Forest Fire News Analysis in Sumatera-Kalimantan in Republika.co.id and Bharian.com.my - Muhammad Ruslan Ramli; Dasad Latif; Youna Chatrine Bachtiar (UIR Press, 2021)
Pollution from smoke haze ignited from forest fires in Indonesia has been a recurrent annual problem among neighboring countries of South East Asia. This study discusses news about forest and land fires in Sumatra and Kalimantan, which were published on republika.co.id and bharian.com.my. This calamity received great attention because of its damaging consequences for other countries. Fires are considered a potential threat to the environmental development because of their effects to the ecosystem and the impact of carbon emission on biodiversity. This study aims to describe news frame republika.co.id and bharian.com.my for forest and land fires in Sumatra and Kalimantan. Using descriptive-qualitative forwarded by Robert Entman's framing analysis model, analyzing the root of the problem, the cause of the problem, moral judgment, and recommendations. Research result revealed differences in attitudes between republika.co.id and bharian.com.my towards this case. On the cause of the problem issue, moral judgment, and recommendations, republika.co.id's judgement are very firm, systematic, and detailed compared to bharian.com.my which appeared to technical and normative ones. On the issue of the root of the problem, the attitude of both of them blamed forest burners and the role of companies as actors.